Mental Health Experiences of Teachers: A Scoping Review - Corrente, Melissa; Ferguson, Kristen; Bourgeault, Ivy Lynn (Journal of Teaching and Learning)

(untitled) (University of Windsor, 2022)
Teacher mental health continues to be of concern in elementary and secondary schools; however, supporting teacher wellbeing is understudied (Parker et al., 2012; Roffey, 2012), particularly from a gender perspective (Bourgeault et al., 2021). Among professionals, teachers exhibit one of the highest levels of job stress and burnout on the job. (Hakanen et al., 2006; Stoeber & Rennert, 2008). This scoping review investigates and consolidates the existing research on teacher mental health, leaves of absences, and return-to-work. Work context and personal factors/family context contribute to teacher stress and attrition and by extension may impact temporary leaves of absence (Pressley, 2021). Several articles report on interventions with moderate success to reduce teacher stress, but no studies evaluated return-to-work interventions (Ebert, 2014; Kwak et al., 2019). The amount of stress teachers are experiencing and the pressure that is causing them to burn out is the most common narrative present in the literature. The review highlights gaps in the literature surrounding teacher mental health, leaves of absence, and return-to-work and a notable gap regarding the role of gender.